Profesor Witold Mańczak – dydaktyk - Anna Bochnakowa (Ksiegarnia Akademicka Publishing, 2019)
Professor Witold Mańczak – an Educator This memoir on Professor Witold Mańczak as an academic teacher opens with a list of grammars and textbooks of the history of Romance languages which he wrote for students of Romance philology. This is followed by a description of Professor’s lectures in historical grammar of Romance languages – erudite but clear, with multiple examples and digressions which widened the scrutinized topic. Also his manner of examining is mentioned, known and strictly defined criteria of evaluation, and its objectivity. Professor’s colleagues from the Institute of Romance Philology like to reminisce his friendly and selfless help and cordiality towards students – beside his attributed severity. Lastly, we emphasize the importance of Professor’s scientific views and methodology in the shaping of academic staff.